Autoimmune Post-Herpes Simplex Encephalitis - Ana B. Chelse; Leon G. Epstein (Pediatric Neurology Briefs Publishers, 2016)
Investigators at August Pi Sunyer Biomedical Research Institute and University of Barcelona performed a prospective surveillance study in 14 patients with immune-mediating relapsing symptoms of post-herpes simplex encephalitis (HSE).